The introduction into sports training - Zahradnik, D.; Korvas, P. (Masaryk University, 2012)
The presented text entitled The Introduction into Sports Training is meant for students of subjects in kinanthropology such as Teaching PE, recreology and coaching etc. Primarily, sports training focuses on cultivating the athlete`s personality; further, it focuses on systematic development of motor abilitites and the process of acquiring motor skills within the specific sports disicpline. It is implemented at different performance and age levels. Features of sports training can be found in various forms. Sports leisure-clubs at elementary schools, sports clubs or still more and more popular commercial sports facilities are an example of this. The personality and professional knowledge of the coach, teacher, trainer or instructor play a crucial part in the quality of sports training implemented. This managining person becomes a personality and a model example to be trusted by his or her trainees, mainy in the youngest age groups. Each coach should attempt to keep main priorities. The most important one goes: "hurt your trainees neither physically nor psychically". Therefore, to meet this principle, the coach must be able to integrate pieces of knowledge accross the fields like anatomy, physiology, biomechanics, psychology, sociology, theory of motor learning and didactics. The present text helps you to basic orientation in the issue of sports training. Individual chapters touch on basic topics necessary for implementation training process in the first stages of sports training. This text should not be understood as a universal manual which can work work with anybody. Rather, it must be viewed as inspiration for furter studies in this difficult, nonetheless beautiful, issue.